2016
DOI: 10.1039/c5fd00167f
|View full text |Cite
|
Sign up to set email alerts
|

From synthetic DNA to PCR product: detection of fungal infections using SERS

Abstract: We report the use of silver hydroxylamine nanoparticles functionalised with single stranded monothiolated DNA for the detection of fungal infections. The four different species of fungi that were targeted were Candida albicans, Candida glabrata, Candida krusei and Aspergillus fumigatus. Rational design of synthetic targets and probes was carried out by carefully analysing the 2-D folding of the DNA and then by global alignment of the sequences to ensure specificity. The effects of varying the concentrations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…26,27 Probe 1 was designed to bind to the five prime (5′) end of the target, whereas probe 2 was constructed to bind to the second half of the target at the three prime (3′) end, with a hexaethylene glycol (HEG) spacer between the end of the DNA probe and the thiol modification. [28][29][30] Nanoparticles were functionalized entirely with either probe 1 or probe 2, and then mixed at a 1:1 volume ratio. If miRNA-17 is present, the target strand is oriented in between two nanoparticles and hybridization to the target draws the nanoparticles close to one another, allowing plasmons to couple and create an area of high energy known as a "hotspot."…”
Section: Overview Of Methodsmentioning
confidence: 99%
“…26,27 Probe 1 was designed to bind to the five prime (5′) end of the target, whereas probe 2 was constructed to bind to the second half of the target at the three prime (3′) end, with a hexaethylene glycol (HEG) spacer between the end of the DNA probe and the thiol modification. [28][29][30] Nanoparticles were functionalized entirely with either probe 1 or probe 2, and then mixed at a 1:1 volume ratio. If miRNA-17 is present, the target strand is oriented in between two nanoparticles and hybridization to the target draws the nanoparticles close to one another, allowing plasmons to couple and create an area of high energy known as a "hotspot."…”
Section: Overview Of Methodsmentioning
confidence: 99%
“…When combined with molecular techniques such as immunoassays and robust chemometrics, SERS is a viable alternative candidate that can compete fairly well with traditional gold-standard techniques in terms of cost but with the additional advantages of portability, rapidity, multiplexing, high specificity, and selectivity. Thus, it is perhaps not surprising that SERS has proliferated into diverse scientific fields for various applications such as clinical, 93,94 discovery of biological and chemical warfare markers, 95 antimicrobial resistance, 96,97 environmental studies, 4,98 and microbial ecology, 99 as shown by the results of a bibliometric analysis of SERS related reports within the last decade ( Figure 3).…”
Section: Classical and Vibrational Spectroscopy Platforms For Bacterimentioning
confidence: 99%
“…This interesting study highlights the ability of SERS to detect trace concentrations of deadly viruses making it a potentially suitable candidate to reveal subclinical and/or asymptomatic infections such as candidemia. 94 With the continuous development of portable Raman spectrometers, SERS can be employed for rapid point-of-care (POC) diagnosis in healthcare especially in rural and remote areas where such infections are highly prevalent. Figure 4 illustrates how SERS fingerprints and principal component analysis (PCA) can be used to differentiate among microbes of clinical and environmental importance.…”
Section: Identification Of Bacteria In Clinical Biochemistrymentioning
confidence: 99%
“…3,4 This general approach is highly selective and sensitive and has been used to create clinically relevant assays. 5 Conversely, direct label-free analysis of DNA or RNA, although it has the advantage of simplicity, is not expected to rival hybridisation-based techniques for sequence determination because of its low positional sensitivity. However, label-free methods do have the distinct advantage that they are intrinsically sensitive to chemical modifications of DNA, since chemical modification of nucleobases causes characteristic changes in their Raman spectra.…”
Section: Introductionmentioning
confidence: 99%